Revisiting essential obstetric care from stakeholders’ view: knowledge and awareness about safe motherhood practices among stakeholders in tertiary care centre - Kshirsagar, Shilpa Pankaj; Karmarkar, Deepti Pushparaj; Damle, Hemant Shrikrishna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: To assess stakeholder’s perception of giving importance to various aspects of antenatal care. Methods: This community based observational study was conducted by Dept. of OBGYN; SKNMC Medical college, Narhe Pune which started from Feb 2016 and culminated on occasion of ‘Safe Motherhood Day’ on 11/04/2016. A poster showing components of safe motherhood was prepared and pregnant patients, their relatives, paramedical staff visiting antenatal OPD were targeted. They were asked to mark the most essential component (in their view) with ‘Bindi’; only one chance was given per participant. Total 2450 women were recruited. Results: Though many women are aware about essential obstetric care, still much emphasis is given on traditional component like diet. There is still unawareness about importance of other components like immunization and intake of iron, calcium tablets or role of investigations or conduction of delivery by trained health care personnel. Conclusions: Knowledge gap found in this study points that easy access to medical care during pregnancy should be improved to have its impact on practices of safe motherhood.